Strategi Komunikasi Marketing Cs Holiday Dalam Menentukan Target Tunggal Pasarnya Di Era New Normal - Adianto, Dedi Anwar (Universitas Majalengka, 2024)
Good management of tour organizer services can improve performance and good results. Tourism is a field that has great potential, so this service sector also includes driving government programs in the creative economy sector. Yogyakarta is known as a cultural city and student city, encouraging Cs Holiday as a tourism service provider to move and take part in this field. A good market population amidst competition for the same services provides its own challenges. Therefore, special strategies are needed to compete in a healthy manner, especially in the post-Covid-19 pandemic period. This research aims to find out the communication strategies used by Cs Holiday in dealing with the pandemic which has subsided. Promotions using various media, both offline and online, are carried out to support marketing strategies by focusing on one target market, namely universities. Through these findings, it is hoped that CS Holiday will continue to be consistent in developing this strategy so that it can continue and reap good results